Effect of alkali metal oxides on reliability and degradation of phosphor-in-glass encapsulants for white LEDs. Issue 8 (June 2016) - Iqbal, Fauzia; Kim, Sunil; Yie, Hoyong; Kim, Yurian; Kim, Hyungsun
Abstract: The effect of alkali metal oxides (Li2 O, Na2 O, and K2 O) on the degradation of remote phosphor-in-glass (PiG) encapsulants for white light-emitting diodes (LEDs) is reported in this paper. Various glass compositions (SiO2 –B2 O3 –ZnO–WO3 –La2 O3 ) with different alkali metal oxides were mixed with phosphor and sintered at appropriate temperatures. These PiG plates were exposed to stress factors, such as current, thermal aging, and an 85°C/85%RH environment, for various holding times. Lumen loss and shift in the Commission Internationale de l'Eclairage (CIE) coordinates of the PiGs were measured after exposure to the stress conditions. Thermal conductivity and thermal quenching behaviors of the PiGs were also studied. The PiG with K2 O shows more stable lumen and CIE values than other glass compositions under current exposure for a short time (10 min); however, its properties are degraded under long periods (1000 h) of 85 °C/85%RH exposure and thermal aging. Choosing the appropriate glass composition can lead to less degradation, thus ensuring a longer lifetime for white LEDs.